KARAKTERISTIK RUMAH TANGGA MISKIN PERKOTAAN DAN PEDESAAN DI SUMATERA BARAT - Ichsan Sevrianda; Dewi Zaini Putri (Universitas Negeri Padang, 2018)
The aims of this study to identify and analyze the impact of education, the number of household members, employment status, and age of household on poverty in West Sumatera. This type of research is associative descriptive research, where the data used was secondary data and cross section, obtained from related institutions, which are analyzed using the Logistic Regression method. The fndings of this study indicate that education, the number of household members, employment status, and age of household have a significant effect on poverty in West Sumatera. Keywords: education, employment status, age of household, poverty, and Logistic Regression